2011
DOI: 10.1002/bdra.22855
|View full text |Cite
|
Sign up to set email alerts
|

Genetic studies of the cystathionine beta‐synthase gene and myelomeningocele

Abstract: BACKGROUND Among infants born with spina bifida, the most common defect is myelomeningocele (MM). The prevention of MM by maternal periconceptual folic acid (FA) supplementation has been extensively studied. The protective effect provided by FA suggests that the genes involved in folate metabolism, such as cystathionine beta-synthase (CBS), warrant further investigation. METHODS This study sequenced the DNA from 96 patients with MM to identify novel potential disease causing variants across the 17 exons of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…These mutations are the first CBS mutations reported in a Filipino patient. The four known SNP found in this study are benign polymorphisms that have been previously described [13][14][15] and were found not to be associated with the disease. …”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…These mutations are the first CBS mutations reported in a Filipino patient. The four known SNP found in this study are benign polymorphisms that have been previously described [13][14][15] and were found not to be associated with the disease. …”
Section: Discussionmentioning
confidence: 48%
“…13 This suggests that presence of the rs706209 SNP in CBS may affect the CBS pre-mRNA splicing prior to CBS mRNA translation, which may lead to an aberrant CBS protein. The functional significance of this, however, still needs to be investigated.…”
Section: Cbs Mutations In Homocystinuria 885mentioning
confidence: 99%
“…CBS rs2851391 was associated with a change in postmethionine load Hcy levels and plasma Hcy levels of subjects with rs2851391 TT genotype were significantly higher compared to that of the TC and CC genotypes . The presence of CBS rs706209 may affect pre‐mRNA splicing, which could generate an aberrant CBS protein and consequently affect Hcy metabolism …”
Section: Discussionmentioning
confidence: 99%
“…A genome‐wide association study in European countries demonstrated that rs2851391 was associated with plasma Hcy . The relationship between CBS rs706209 and folate/Hcy metabolism was also investigated . However, there were no studies on the connection about these single nucleotide polymorphisms (SNPs) with the efficacy of folate treatment for HHcy.…”
Section: Introductionmentioning
confidence: 99%
“…The CBS gene is localized at 21q22.3 and spans over 30 kb and consists of 23 exons [21]. So far, more than hundreds of mutations in CBS gene had been identified, the major of which are missense mutations and correlated with homocystinuria.…”
Section: Rs2850144 Polymorphism Of the Cbs Genementioning
confidence: 99%